La lucha por el derecho a aparecer en las márgenes del río Amazonas : activismo, organización y acción política LGBT en la triple frontera entre Brasil, Perú y Colombia. - Néstor Eliécer Moreno Rangel (2020)
In the threefold Amazonian border (referred to as TF by its Spanish acronym) -which is situated as a transnationally social and geographic area, mutual and differentiating, understood as part of a merged, marginal, and marginalized territory in the South American outskirts- and by means of several interviews with activists, whose involvement and participations -hand in hand with existing LGBT organizations- in diverse, implemented actions, the recognition of litigation is carried out in favor of the vindication of rights and the homophobia confrontation, along with other forms of prejudice related to sexual orientation and gender in the triple frontier. Accounts, which have been built in this particular scene, are arrayed to dialogues with approaches from the plural and radical democratic theory (TDR by its Spanish initials) -particularly, the idea of politics as action and rarity and the historical existence of hegemonic regimes- and the gender norms concept to ultimately analyze politics as a response that contributes to a turnaround and from which every establishment is susceptible to be challenged and changed. The foregoing strongly related to social dynamics, institutional practices, and the LGBT community’s access to equal rights and opportunities in this transnational location of the world and also its relation to the conservative and heteronormative dominance and hegemony that are currently ruling in our Latin American areas. The LGBT movement plays an important role in the Amazonian frontier; their everyday actions as an organization are materialized to vindicate those existences that do not adjust to a system that penalizes and restricts male and female ways of being and behaving, and we see these restrictions brought to life by important figures and in acting associations that are direct models of the local governments and national programs. However, -beyond the relation between the Establishment and the LGBT community and as a political expression and manifestation of organizational processes- the movement mainly operates as an internal referent that promotes and encourages processes of identification and affiliation on the basis of co-formation and self-referral. Finally, -without disregarding that in some occasions these aforementioned actions fall into client and bureaucratic practices or, aslant, into democratic liberalism and with this the statement that claims the socioeconomic level is the main indicator of guarantees, approaches, and rights in our societies- we consider this fight as a courageous, enthusiastic, and creative one that in the region of the threefold Amazonian border is being waged with bravery and fondness.